The time structure Within of the stream of consciousness For Anisa Abboud and Ghada Assaman - Maya, Fakher; Jaber, Youssef; Alhafi, Houda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research highlights on the presence of the time in the stream of consciousness and clarifies its role in making the mind full of bright ideas and thoughts clarifying the complex human relation with time and how the human mind smashes this logical sequence of time displaying various sides of times according to invisible content hard to be understood bylletraditional way of writing and this forces a new reasoning explains the interferes of several time dimensions. And it is known to everyone that this has a great effect in knowing what secrets self covers as well as confirming the self-understanding of the time and proving that time isn't existed far from the self that realizes it.